Pengaruh Promosi Dan Harga Terhadap Loyalitas Pelanggan Pada Happy Puppy Bintaro Tangerang - Putri Damayanti; Sinta Sulistiani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine the effect of promotion and price on consumer loyalty at Happy Puppy Bintaro Tangerang, both partially and simultaneously. The research method used is a quantitative approach with a sample of 99 respondents. The data analysis techniques in this study include validity testing, reliability testing, normality testing, multicollinearity testing, autocorrelation testing, heteroscedasticity testing, simple linear regression, multiple linear regression, correlation coefficient analysis, coefficient of determination, t-test, and F-test. The results show that, partially, the promotion variable has a positive and significant effect on consumer loyalty, with a calculated t-value of 14.885 greater than the t-table value of 1.985 and a significance value of 0.000 < 0.05. The price variable also has a positive and significant effect on consumer loyalty, as evidenced by a calculated t-value of 7.953 > 1.985 and a significance value of 0.000 < 0.05. Simultaneously, both variables have a positive and significant effect on consumer loyalty, as indicated by a calculated F-value of 125.570 > 3.09 and a significance value of 0.000 < 0.05. Therefore, this study concludes that promotion and price, both partially and simultaneously, have a significant effect on consumer loyalty at Happy Puppy Bintaro Tangerang Keywords: Promotion, Price, Consumer Loyalty